A novel active-passive sampling approach for measuring time-averaged concentrations of pollutants in water. (October 2018) - Amato, Elvio D.; Covaci, Adrian; Town, Raewyn M.; Hereijgers, Jonas; Bellekens, Ben; Giacometti, Valentina; Breugelmans, Tom; Weyn, Maarten; Dardenne, Freddy; Bervoets, Lieven; Blust, Ronny
Abstract: Passive sampling with in situ devices offers several advantages over traditional sampling methods (i.e., discrete spot sampling), however, data interpretation from conventional passive samplers is hampered by difficulties in estimating the thickness of the diffusion layer at the sampler/medium interface ( δ ), often leading to inaccurate determinations of target analyte concentrations. In this study, the performance of a novel device combining active and passive sampling was investigated in the laboratory. The active-passive sampling (APS) device is comprised of a diffusion cell fitted with a pump and a flowmeter. Three receiving phases traditionally used in passive sampling devices (i.e., chelex resin, Oasis HLB, and silicone rubber), were incorporated in the diffusion cell and allowed the simultaneous accumulation of cationic metals, polar, and non-polar organic compounds, respectively. The flow within the diffusion cell was accurately controlled and monitored, and, combined with diffusion coefficients measurements, enabled the average δ to be estimated. Strong agreement between APS and time-averaged total concentrations measured in discrete water samples was found for most of the substances investigated. Accuracies for metals ranged between 87 and 116%, except Cu and Pb (∼50%), whilst accuracies between 64 and 101%, and 92 and 151% were achieved for polar and non-polar organic compounds, respectively. These results indicate that, via a well-defined in situ preconcentration step, the proposed APS approach shows promise for monitoring the concentration of a range of pollutants in water. Highlights: A novel sampler is developed for simultaneous accumulation of metals and organic compounds from aquatic systems. The water diffusion layer thickness is controlled by regulation of the flow through the device. Deployment times of 48 h are sufficient to detect environmentally relevant concentrations in artificial freshwater.